Preference and determinants of delivery mode in pregnant women with one cesarean scar: a cross-sectional study in two urban Ugandan public hospitals - Brenda Nabawanuka; Tom Ngabirano; Joyce Nankumbi (BMC Pregnancy and Childbirth)
Abstract Background The number of cesarean sections among women with a previous scar has continued to increase in Uganda. Such women can opt for a trial of labor, and the success rate for spontaneous vaginal delivery is 60–80%. This study assessed the preference and determinants of delivery mode among pregnant women with one cesarean scar. Methods A cross-sectional analytical study was conducted among pregnant women who were attending antenatal care in two public hospitals in Uganda from 1st September to 1st October 2022. Kish Lisle formula was used to get a total sample of 169 pregnant women with one previous scar and nonrecurring indication for cesarean section. These were consecutively recruited into the study, and a modified Poisson regression was performed to identify factors associated with the preferred mode of delivery. Results The mean age of the participants was 28 (4.88) years. Out of 169 women, the majority 137 (81%) preferred a trial of labor. Mothers who preferred to have more than four children were more likely to opt for a trial of labor (aPVR = 0.27, CI;1.01–1.49, p = 0.009). Mothers who were concerned about the cost associated with cesarean section were more likely to choose a trial of labor (aPVR = 1.2, CI;1.01–1.49, p = 0.03), and mothers who perceived that a cesarean section affects body image (aPVR = 3.06, CI;1.39–6.75, p = 0.03) and being employed (aPVR = 0.84, CI:0.74–0.96, p = 0.01) were more likely to prefer a cesarean section. Conclusion Trial of labor after cesarean remains the preferred mode of delivery among women. The desire to have more children and concern about medical expenses increased the likelihood of having a vaginal birth preference. Women with body image concerns and being employed increased the likelihood of a cesarean section preference. It is recommended to consider a trial of labor after cesarean section for all women with nonrecurring indications for cesarean section. Empowering women through health education on the risks and benefits of cesarean section helps them make an informed choice.